AI-POWERED STORY CREATION: TRANSFORMING AGILE DEVELOPMENT IN THE INSURANCE INDUSTRY - Chetan Prakash Ratnawat (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The insurance industry's digital transformation faces significant challenges in converting complex business requirements into actionable development tasks. This comprehensive article examines how AI-powered story creation tools are revolutionizing the traditional approach to requirement engineering in insurance software development. Through advanced natural language processing and machine learning capabilities, these systems demonstrate remarkable improvements in processing efficiency, accuracy, and compliance adherence. The article explores the technical framework, industry-specific applications, and implementation benefits of AI-powered story creation tools across underwriting, claims processing, and agent support systems. The article encompasses key technological considerations, including security implementations and performance optimizations, while providing insights into future developments that will further transform insurance technology development practices.